Dietary Calcium Intake, Vitamin D Status, and Bone Health in Postmenopausal Women in Rural Pakistan (Journal of Health, Population and Nutrition, 2011)
The high prevalence of osteoporosis in Pakistan is of public-health concern. However, there is a paucity of information regarding nutrition and bone density in rural communities. The purpose of this study was to evaluate the dietary and lifestyle factors that impact bone health in Nahaqi. Data were collected from 140 postmenopausal women using an interviewer-administered 24-hour dietary recall questionnaire. Bone mineral density was estimated using the quantitative ultrasound index (QUI). Serum 25(OH)D was measured in fasting blood samples. The QUI scores revealed that 42% and 29% of the women had T-scores, indicative of osteopaenia and osteoporosis respectively. The mean calcium intake was 346 mg/d, which is less than 50% of the recommended daily intake. The QUI correlated with 25(OH)D after controlling for age (p=0.021, r=0.41, r2=0.168). Vitamin D deficiency and low intake of dietary calcium are two key factors contributing to poor bone health in this population. Key words: Bone health; Bone mineral density; Calcium; Osteoporosis; Quantitative ultrasound index; 25(OH)D; Vitamin D deficiency; Pakistan DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8900 JHPN 2011; 29(5): 465-470